The Impact of Corporate Social Responsibility on Achieving a Competitive Advantage: Evidence from Toms Company - Joanna GRZEGORCZYK (Communications of International Proceedings, 2021)
The aim of the article is to present the concept of corporate social responsibility (CSR) and to indicate the importance of CSR in achieving a competitive advantage by a company. The study presents the theoretical foundations of corporate social responsibility, discusses possible areas of corporate involvement, and presents numerous benefits resulting from the implementation of this concept. The most important profit resulting from long-term, well-thought-out and consistent CSR activities is the achievement of a competitive advantage on the market. The article is supplemented with a description of the TOMS company, which has identified itself with the principles of corporate social responsibility from the beginning of its activity.
Keywords: Corporate Social Responsibility; CSR; Competitive Advantage